Analisis Manajemen Risiko dalam Rantai Pasok Usaha Rempah-Rempah Sailiwa Product - Putri Ayuningtyas; Tania Kirana Aprilia; Asep Suwarna (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This research aims to analyze the implementation of risk management in Sailiwa Product, a small-scale business engaged in the processing and distribution of spices. The main problem identified is the lack of systematic risk management practices, which often lead to operational disruptions, inconsistent supply from farmers, and quality issues in stored products. This study employs a qualitative descriptive method using observation and interviews to explore how the business owner identifies, mitigates, and manages various types of risks. The data collected were analyzed interactively through data reduction, presentation, and conclusion drawing. The results indicate that Sailiwa Product has begun implementing basic risk control strategies such as dual verification systems, safety stock preparation, and better product storage methods. These simple yet adaptive steps have positively impacted business continuity. The study suggests that the adoption of a digital inventory system and periodic risk evaluation could further enhance the effectiveness of risk management in the future.